1999
DOI: 10.1152/jn.1999.81.3.1184
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Activation of Presynaptic GABAB Receptors in the Opener Neuromuscular Junction of Crayfish

Abstract: Release of excitatory transmitter from boutons on crayfish nerve terminals was inhibited by (R,S)-baclofen, an agonist at GABAB receptors. Baclofen had no postsynaptic actions as it reduced quantal content without affecting quantal amplitude. The effect of baclofen increased with concentration producing 18% inhibition at 10 microM; EC50, 50% inhibition at 30 microM; maximal inhibition, 85% at 100 microM and higher. There was no desensitization, even with 200 or 320 microM baclofen. Phaclofen, an antagonist at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Another explanation could be activation of a GABA B receptor. GABA B receptors have been indicated to inhibit transmitter release from crayfish excitor motor terminals (Fischer and Parnas, 1996a,b;Parnas et al, 1999). The apparent persistence of inhibition for a few hundred milliseconds after the offset of inhibitor axon firing (Fig.·2D) would be consistent with the decay of a GABA B -mediated contribution to inhibition.…”
Section: Increased Inhibition Later In Trainssupporting
confidence: 56%
See 1 more Smart Citation
“…Another explanation could be activation of a GABA B receptor. GABA B receptors have been indicated to inhibit transmitter release from crayfish excitor motor terminals (Fischer and Parnas, 1996a,b;Parnas et al, 1999). The apparent persistence of inhibition for a few hundred milliseconds after the offset of inhibitor axon firing (Fig.·2D) would be consistent with the decay of a GABA B -mediated contribution to inhibition.…”
Section: Increased Inhibition Later In Trainssupporting
confidence: 56%
“…Inhibition mediated by GABA B receptors has been reported (Parnas et al, 1999) but we could find no inhibitory effect of baclofen (30-180·µmol·l -1 ; N=4) on excitatory transmission, and baclofen did not occlude inhibition of the EJP by the inhibitor axon nor remove the reduced build-up of facilitation during short trains. Therefore, our data suggest that GABA A -mediated presynaptic inhibition With the inhibitor stimulated in the standard manner (left-hand traces; eight inhibitor stimuli at 100·Hz), inhibition was 13±2% (mean ± S.E.M.…”
Section: Increased Inhibition Later In Trainscontrasting
confidence: 50%
“…presynaptic GABA B R-mediated inhibition has also been reported in some other preparations (Le Feuvre et al, 1997;Parnas et al, 1999), suggesting that ambient GABA can suppress synaptic GABA release. In the present study, we have shown that GABA B R activation/block only alters GABA release probability without affecting the RRP or mIPSC amplitudes.…”
mentioning
confidence: 62%
“…Although the evidence is still sketchy, it currently appears that most mammalian neurotransmitter receptors have counterparts in invertebrates (337). Invertebrate GABA B receptors were described in echinoderms (90,91), mollusks (11,287), and arthropods (101,226,254,276,335). Invertebrate GABA B functions were mostly studied at the neuromuscular junction of echinoderms, where GABA elicits inhibitory and excitatory responses (90).…”
Section: Invertebrate Gaba B Receptorsmentioning
confidence: 99%